Perwujudan Perlindungan Hukum Bagi Perempuan dalam Praktik Kawin Tangkap - Ginting, Gladies Agina; Lewoleba, Kayus Kayowuan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Captive marriage, which involves the forced taking of women without their consent, goes against the principles enshrined in the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Universal Declaration of Human Rights (UDHR). Although Indonesian law prohibits kidnapping and forced marriage, cultural acceptance of these practices on Sumba makes it difficult to enforce the law. This study underscores the need for increased law enforcement, comprehensive public education, robust support services for victims, policy reform, and active engagement with traditional institutions. Such steps are critical to protecting women's rights and aligning domestic practices with international human rights standards.